Children with Small Chests. Issue 251 (February 1972) - Hull, D.; Barnes, N. D.
Abstract : The volume of the thoracic cage may be severely restricted by faulty rib growth due to a variety of bone diseases. At one extreme the thorax may be too small to permit adequate lung expansion after birth; at the other, the abnormality may only be recognized by examination of an x -ray. However, in a small group of infants the deformity, though not obvious clinically, may be severe enough to cause fatal respiratory failure in the first few months of life. It is possible that some of these infants may be saved by surgical enlargement of the thoracic cage.